2018
DOI: 10.3389/fimmu.2018.02004
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanisms of IL-33-ST2-Mediated Allergic Inflammation

Abstract: Interleukin-33 (IL-33) plays multiple roles in tissue homeostasis, prevention of parasitic infection, and induction of allergic inflammation. Especially, IL-33-ST2 (IL-1RL1) axis has been regarded as the villain in allergic diseases such as asthma and atopic dermatitis and in autoimmune diseases such as rheumatoid arthritis. Indeed, a number of studies have indicated that IL-33 produced by endothelial cells and epithelial cells plays a critical role in the activation and expansion of group 2 innate lymphoid ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 74 publications
1
68
0
2
Order By: Relevance
“…IL-33 is a key cytokine involved in type 2 immunity and released upon cell necrosis and drives inflammation as a damage-associated molecular pattern. IL-33 can bind to ST2, a member of the IL-1 receptor family, activates NF-κβ and MAPK, promotes the production of Th2 cytokines, and participates in allergy [23]. A study found that a marked increase in levels of IL-33 in severe patients (including myoclonus, vomiting, ataxia, irritability, and hypersomnia) and critical cases (quickly developed acute respiratory failure and PE) presenting with neurological manifestations compared to mild patients [24].…”
Section: Il-33mentioning
confidence: 99%
“…IL-33 is a key cytokine involved in type 2 immunity and released upon cell necrosis and drives inflammation as a damage-associated molecular pattern. IL-33 can bind to ST2, a member of the IL-1 receptor family, activates NF-κβ and MAPK, promotes the production of Th2 cytokines, and participates in allergy [23]. A study found that a marked increase in levels of IL-33 in severe patients (including myoclonus, vomiting, ataxia, irritability, and hypersomnia) and critical cases (quickly developed acute respiratory failure and PE) presenting with neurological manifestations compared to mild patients [24].…”
Section: Il-33mentioning
confidence: 99%
“…SR9009 significantly inhibited IgE-and IL-33-mediated mast cell activation ( Figure 2). The Gab2/PI3K pathway is critical in FcεRI signaling leading to degranulation in mast cells [22] and the NF-κB pathway mediates IgE-or IL-33-mediated transcriptonal activation of cytokine gene expression [5,6,20,21]. Thus, it is likely that SR9009 and other synthetic REV-ERB agonists inhibited IgE-mediated degranulation and IgE-and IL-33-mediated IL-6 and IL-13 expression through the suppression of the Gab2/PI3K and NF-kB pathways, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, the effects of SR9009 on IgE-or IL-33-mediated mast cell activation were examined when REV-ERBs expression were knocked-down by specific siRNAs in wild-type BMMCs. Both the NF-κB and p38 MAPK pathways mediate IgE-or IL-33-mediated transcriptonal activation of cytokine gene expression [5,6,20,21]. SR9009 inhibited IgE-and IL-33-induced phosphorylation of p65, a subunit of NF-κB, but did not affect IgE-or IL-33-induced phosphorylation of p38 MAPK in wild-type BMMCs (Figure 3a).…”
Section: Sr9009 May Inhibit Ige-and Il-33-mediated Mast Cell Activatimentioning
confidence: 97%
See 1 more Smart Citation
“…Identified as an alarmin and a nuclear factor controlling gene transcription, it warns immune system of barrier injury. The major targets of IL-33 appear to be mast cells, eosinophils, group 2 innate lymphoid cells (ILC2s), Th2 cells, regulatory T cells (Tregs), natural killer cells (NK), basophils, dendritic cells and alternatively activated macrophages, since ST2 is mainly expressed on these cells [34]. Large amounts of IL-5 and IL-13 are secreted by ILC2s responding to IL-33.…”
Section: Il-33/il-31 Axismentioning
confidence: 99%